Aspek-AspekPenyakit Perdarahan Dalam Praktek Pada Anak - Sunarto Sunarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Hemorrhagic diathesis in pediatrics, covering the mechanism of hemostasis and the diagnostic and therapeutic aspects, is discussed.Hemorrhagic cases due to various causes are not uncommon in children. It is essential to understand aspects of hemorrhagic diathesis to be able to manage such cases efficiently. The diagnostic approach should be in an ordered fashion. By such a way and by understanding the principles of management, even with limited facilities, we can diagnose and treat many cases and at least recognize difficult cases and act appropriately before referring.Key Words: hemorrhagic diathesis - mechanism of hemostasis - hemophilia - purpura - hypoprothrombinemia